2012
DOI: 10.6026/97320630008098
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of miRNAs and their targets from the expressed sequence tags of Raphanus sativus

Abstract: MicroRNAs (miRNAs) are a novel growing family of endogenous, small, non- coding, single-stranded RNA molecules directly involved in regulating gene expression at the posttranscriptional level. High conservation of miRNAs in plant provides the foundation for identification of new miRNAs in other plant species through homology alignment. Here, previous known plant miRNAs were BLASTed against the Expressed Sequence Tag (EST) database of Raphanus sativus, and according to a series of filtering criteria, a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Similar ranges of pre-miRNA length have been found in other plant species (Qiu et al, 2007;Din and Barozai, 2014;Muvva et al, 2012), although the average size often varies among studies. Length diversity and sequence differences are canonical features of precursors because each is transcribed from a different gene (Starega-Roslan et al, 2011).…”
Section: Discovery Of Pre-mirnas From Pineapple Est Librariessupporting
confidence: 67%
“…Similar ranges of pre-miRNA length have been found in other plant species (Qiu et al, 2007;Din and Barozai, 2014;Muvva et al, 2012), although the average size often varies among studies. Length diversity and sequence differences are canonical features of precursors because each is transcribed from a different gene (Starega-Roslan et al, 2011).…”
Section: Discovery Of Pre-mirnas From Pineapple Est Librariessupporting
confidence: 67%
“…Although a few miRNAs targets from radish have been previously predicted (Muvva et al ., 2012; Xu et al ., 2013), no miRNA targets for radish have yet been experimentally characterized. In this study, the miRNA-cleaved mRNAs in radish were first systematically confirmed using the high-throughput degradome sequencing technology.…”
Section: Resultsmentioning
confidence: 99%
“…With a comparative analysis approach, 48 conserved miRNAs belonging to nine miRNA families were isolated from the expressed sequence tag (EST) databases of R. sativus (Muvva et al ., 2012). Moreover, Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The different criteria were used to screen precursor miRNAs based on statistical comparative genomics approaches reported by Zhang et al, 2006 [42], which had already been adopted in many ESTs targeted miRNAs identification and characterization studies [43,44,45]. Here, only candidate ESTs sequences adopted the following criteria were prioritized as considerable miRNAs in C. capsularis: (1) not more than 3 mismatches were allowed in the putative miRNAS with all previously known plant miRNAs; (2) the length of predicted mature miRNAs should be in the range of 18 nucleotides; (3) pre-miRNA sequence must fold into an appropriate hairpin secondary structure and mature miRNA should be located in one arm of the hairpin stem-loop secondary structure; (4) the mature miRNAs should allow less than 3 mismatches with the opposite miRNA strand in the other arm; (5) A+U content of pre-miRNA must be in range of 30% to 70%,; and (6) the secondary structure of mature miRNAs must have lower minimal (highly negative) folding free energy (MFE) and minimal free energy index (MFEI) value [46,47,48].…”
Section: Identification Of Novel Mirnas With Reported Criteriamentioning
confidence: 99%